Oxide solid electrolyte membrane carrier and preparation method thereof
By setting a base, a functionalized adhesive layer and a silicone grafted resin layer on the oxide solid electrolyte carrier, the problems of shrinkage, warping and peeling of the oxide solid electrolyte membrane during the coating process are solved, the formation of high-quality membranes and easy tearing are achieved, and the coating effect is improved.
Patent Information
- Application Number
- CN202410304046.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-03-18
- Publication Date
- 2025-09-26
AI Technical Summary
Oxide solid electrolyte membranes have problems such as overflow, cohesion, warping and peeling during the preparation process, and the existing carrier material and the electrolyte membrane surface energy do not match, making it difficult to effectively coat and tear off.
An oxide solid electrolyte carrier structure including a substrate, a functionalized adhesive layer and a silicone grafted resin layer is adopted. The functionalized bite force is provided by the adhesive layer to combine the substrate and the resin layer, forming a characteristic surface energy that matches the oxide solid electrolyte, thereby achieving effective coating and tearing.
The shrinkage, warping and peeling problems of the oxide solid electrolyte membrane are solved, the coating quality is ensured, and the oxide solid electrolyte membrane can be easily torn off without damage, realizing the formation of high-quality membranes.
Smart Images

Figure CN120709468A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of solid electrolytes, and in particular to an oxide solid electrolyte membrane carrier and a preparation method thereof. Background Art
[0002] Compared to traditional liquid lithium-ion batteries, all-solid-state lithium-ion batteries (ALLBs) have attracted increasing attention in recent years due to their superior safety, high energy density, and excellent cycling performance. Solid-state electrolytes, as the core material in ALLBs, directly determine their performance. Oxide solid-state electrolytes offer numerous advantages, including high ionic conductivity, a wide electrochemical window, high mechanical strength, and stability to air and metallic lithium, making them promising solid-state electrolytes.
[0003] However, during the preparation process of oxide solid electrolyte membranes, after the oxide solid electrolyte is dispersed in the formulated colloid, it exhibits cohesive forces. This makes coating onto existing carriers very susceptible to macroscopic changes such as overflow and cohesion, preventing effective coating to form high-quality membranes. This, in turn, leads to problems such as shrinkage, warping, and peeling of the oxide solid electrolyte membrane. Furthermore, the surface energy mismatch between existing carriers and oxide electrolyte membranes makes it difficult to remove the oxide electrolyte membrane from the carrier, and removal can cause structural damage to the solid electrolyte membrane. Summary of the Invention
[0004] In view of this, it is indeed necessary to provide an oxide solid electrolyte carrier, which can solve the above technical problems.
[0005] An oxide solid electrolyte membrane carrier comprises a substrate, a first coating layer and a second coating layer, wherein the first coating layer is coated on the surface of the substrate, and the second coating layer is coated on the surface of the first coating layer, the first coating layer is an adhesive layer, and the second coating layer is a resin layer.
[0006] Preferably, the first coating is a functionalized adhesive layer.
[0007] Preferably, the first coating layer is a polyethyleneimine (PEI) layer.
[0008] Preferably, the second coating layer is a silica gel grafted resin layer.
[0009] Preferably, the second coating layer is a silica gel grafted acrylic resin (methyl acrylate).
[0010] Preferably, the second coating layer is polysiloxane-grafted acrylic resin.
[0011] A method for preparing the above-mentioned oxide solid electrolyte membrane carrier comprises the following steps:
[0012] Step S1, providing the substrate, an adhesive and a resin material;
[0013] Step S2, coating the adhesive on the surface of the substrate and baking to form the first coating; and
[0014] Step S3: coating the resin material on the surface of the first coating layer, and baking to form the second coating layer, thereby obtaining the oxide solid electrolyte carrier.
[0015] Compared to the prior art, the oxide solid electrolyte carrier provided by the present invention includes a substrate, an adhesive layer, and a resin layer. The adhesive layer provides functionalized bite force, appropriately bonding the substrate and the resin layer, so that the carrier exhibits a characteristic surface energy that matches that of the oxide solid electrolyte. This allows the oxide solid electrolyte colloid to be effectively coated and bite-bonded on the surface of the oxide solid electrolyte carrier, and then, through a series of baking processes, forms an oxide solid electrolyte film on the surface of the carrier. The oxide solid electrolyte film can be effectively attached to the carrier, and experiments have shown that it does not produce problems such as shrinkage, warping, peeling, and baking beam marks. Moreover, the oxide solid electrolyte film can be easily torn off from the carrier without causing structural damage to the oxide solid electrolyte film. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1 A schematic structural diagram of an oxide solid electrolyte membrane carrier provided in an embodiment of the present invention.
[0017] Figure 2 This is a photograph of the lithium lanthanum zirconium oxide solid electrolyte being coated on the surface of a carrier in Example 1 of the present invention.
[0018] Figure 3 This is a photograph of the lithium lanthanum zirconium oxide solid electrolyte being coated on the surface of a carrier in Example 2 of the present invention.
[0019] Description of main component symbols
[0020] Oxide solid electrolyte carrier 100
[0021] Base 102
[0022] First coating 104
[0023] Second coating 106
[0024] The following specific embodiments will further illustrate the present invention in conjunction with the above-mentioned drawings. DETAILED DESCRIPTION
[0025] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art in the art of the present application. The terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the present application.
[0026] In addition, descriptions such as "first" and "second" in this application are for descriptive purposes only and cannot be understood as indicating or implying their relative importance or implicitly indicating the number of technical features indicated. Thus, features defined as "first" and "second" may explicitly or implicitly include at least one of the features. The terms used herein are only used to describe specific embodiments and are not intended to limit the embodiments. Expressions used in the singular include expressions in the plural unless it has a clearly different meaning in the context. In this specification, the terms "including", "having" and / or "configured to" indicate the presence of the listed features, wholes, steps, operations, components and / or structures, and do not exclude the presence or addition of one or more features, wholes, steps, operations, components, structures and / or their collections.
[0027] Furthermore, the numerical values recited herein are included within a permissible range of deviation for the particular value as determined by one of ordinary skill in the art to take into account errors associated with measuring the particular quantity (e.g., limitations of the measurement system). For example, this may mean within one or more standard deviations, or within ±20%, 10%, or 5% relative to the recited value.
[0028] The following will further describe in detail the oxide solid electrolyte membrane carrier and its preparation method provided by the present invention in conjunction with the accompanying drawings and specific embodiments. The following embodiments and features thereof may be combined with each other unless they conflict.
[0029] See also Figure 1 The present invention provides an oxide solid electrolyte carrier 100 (hereinafter referred to as carrier 100) for supporting an oxide solid electrolyte membrane. The carrier 100 includes a substrate 102, a first coating 104, and a second coating 106. The first coating 104 is applied to the surface of the substrate 102, and the second coating 106 is applied to the surface of the first coating 104. The first coating 104 is disposed between the substrate 102 and the second coating 106.
[0030] The substrate 102 is made of a material that is heat-resistant and has a low shrinkage rate at high temperatures, such as polyethylene terephthalate (PET), polyimide (PI), polypropylene (PP), propylene oxide (PO), triacetyl cellulose (TAC), cycloolefin polymer (COP), etc. Preferably, after the substrate 102 is maintained at a temperature of 160° C. or higher for 10 minutes, the thermal shrinkage rate in both the machine direction (MD) and the transverse direction (TD) is less than 0.5.
[0031] The thickness of the substrate 102 is preferably in the range of, but not limited to, 120-130 μm.
[0032] The substrate 102 has good mechanical properties. Preferably, the longitudinal tensile strength MD of the substrate 102 is greater than 18 N / m. 2 , transverse tensile strength TD>23.5N / m 2 .
[0033] The coefficient of friction of the substrate 102 is preferably greater than 0.4 μs. The wettability index of the outer surface of the substrate 102 is preferably greater than 55, and the wettability index of the inner surface is preferably less than 42, wherein the outer surface refers to the surface of the substrate 102 that is not in contact with the first coating 104, and the inner surface refers to the surface of the substrate 102 that is in contact with the first coating 104.
[0034] In this embodiment, the substrate 102 is a PET sheet with a thickness of 125 μm and a tensile strength MD>18 N / m 2 , TD>23.5N / m 2 ; The friction coefficient is greater than 0.4μs; the transverse and longitudinal thermal shrinkage rates are both less than 0.5; the outer surface wettability index is greater than 55; the inner surface wettability index is less than 42.
[0035] The first coating layer 104 is a bonding layer for increasing the bonding strength between the substrate 104 and the second coating layer 106. The thickness of the first coating layer is preferably, but not limited to, 0.5-2 μm.
[0036] Preferably, the first coating 104 is a functionalized adhesive layer. More preferably, the first coating 104 is a polyethyleneimine (PEI) functionalized adhesive layer. The PEI functionalized adhesive layer provides functionalized bite force, properly bonding the substrate 102 and the second coating 106, so that the carrier 100 exhibits a characteristic surface energy that matches the oxide solid electrolyte, allowing the oxide solid electrolyte colloid to be effectively coated and bite on the surface of the carrier 100. After a series of baking processes, an oxide solid electrolyte film is formed on the surface of the carrier 100, and the oxide solid electrolyte film can be effectively attached to the carrier 100.
[0037] In this embodiment, the first coating layer 104 is a polyethyleneimine (PEI) layer, the polymerization degree of PEI is about 90-110, and the monomer molecular weight is 43; the thickness of the adhesive layer is 1 μm.
[0038] The thickness of the second coating layer 106 is preferably but not limited to 10-12 μm.
[0039] The second coating layer 106 is a resin layer. Preferably, the second coating layer is a silicone-grafted resin layer. The mass ratio of silicon in the silicone-grafted resin layer is preferably 1% to 3%. More preferably, the second coating layer is a silicone-grafted acrylic resin (methyl acrylate). In this embodiment, the second coating layer 106 is a polysiloxane-grafted acrylic resin.
[0040] The carrier material 100 is preferably used for oxide ceramic solid electrolyte membranes. For example, it can be applicable to, but not limited to, lithium lanthanum zirconium oxide (LLZO) solid electrolyte membranes, lithium aluminum titanium phosphate (LATP) solid electrolyte membranes, lithium aluminum germanium phosphate (LAGP) solid electrolyte membranes, and lithium lanthanum titanate (LLTO) solid electrolyte membranes.
[0041] The following describes the carrier 100 of the present invention by taking an LLZO solid electrolyte membrane as an example through specific embodiments and comparative examples.
[0042] Example 1:
[0043] In this embodiment, the oxide solid electrolyte is a lithium lanthanum zirconium oxide (LLZO) solid electrolyte gel. The mass proportion of LLZO particles in the LLZO solid electrolyte gel is 5-45%, and the cumulative particle size distribution percentage of the LLZO particles is D50 < 50nm; D90 < 200nm. The LLZO solid electrolyte gel contains a polymer, which is a mixture of PVDF1, PVDF2, PVDF3, PMMA, and LiTFSI, wherein PVDF1 is greater than 200 million Da; PVDF2 is greater than 1 million Da; and PVDF3 is greater than 300,000 Da. The mass percentage of each component in the polymer is 0-30% for PVDF1; 0-30% for PVDF2; 0-30% for PVDF3; 0-10% for PMMA; and 0-25% for LiTFSI. The solvent in the LLZO solid electrolyte gel is: dimethylacetamide (DMAC): N-methylpyrrolidone (NMP): tetrahydrofuran (THF): butanone (MEK): toluene = (70-85): (1-10): (1-15): (1-7): (1-5).
[0044] In this embodiment, the substrate 102 in the carrier 100 is a PET sheet with a thickness of 125 μm and a tensile strength MD>18 N / m 2 , TD>13N / m 2The friction coefficient is greater than 0.4 μs; the transverse and longitudinal thermal shrinkage rates are both less than 0.5; the outer surface wettability index is greater than 55; and the inner surface wettability index is less than 42. The first coating 104 is polyethyleneimine (PEI), with a degree of polymerization of approximately 90-110 and a monomer molecular weight of 43. The adhesive layer thickness is 1 μm. The second coating 106 is a polysiloxane-grafted acrylic resin, wherein the mass percentage of silicon in the polysiloxane-grafted acrylic resin is approximately 1%.
[0045] The LLZO solid electrolyte gel is coated on the surface of the carrier 100 and then dried at a drying temperature of 160° C. and a drying time of 10 minutes, thereby obtaining an LLZO solid electrolyte membrane adhered to the surface of the carrier 100 .
[0046] Example 2:
[0047] This embodiment is substantially the same as embodiment 1, with the only difference being that the mass percentage of silicon in the second coating layer 106 is 3%.
[0048] Example 3:
[0049] This embodiment is substantially the same as embodiment 1, with the only difference being that the mass percentage of silicon in the second coating layer 106 is 5%.
[0050] Comparative Example 1:
[0051] The comparative example 1 is substantially the same as the embodiment 1, with the only difference being that the second coating 106 in the comparative example is an acrylic adhesive system of silica gel grafted with fluorine, specifically perfluorooctyltriethoxysilane+propyltrimethoxysilane, wherein the mass percentage of fluorine is 0.4%.
[0052] Comparative Example 2:
[0053] The comparative example is substantially the same as comparative example 1, except that the mass percentage of fluorine is 0.7%.
[0054] Comparative Example 3:
[0055] The comparative example is substantially the same as comparative example 1, except that the mass percentage of fluorine is 0.8%.
[0056] Comparative Example 4:
[0057] The comparative example is substantially the same as comparative example 1, except that the mass percentage of fluorine is 0.9%.
[0058] Comparative Example 5:
[0059] The comparative example is substantially the same as comparative example 1, except that the mass percentage of fluorine is 1.0%.
[0060] Comparative Example 6:
[0061] Comparative Example 6 is basically the same as Example 1, with the only difference being that the second coating 106 in the comparative example is a fluorine-grafted silica gel system, specifically silica gel grafted fluorine-perfluorooctyltriethoxysilane + propyltrimethoxysilane, and the mass percentage of fluorine is 1.0%.
[0062] Table 2 shows the performance of the carriers with LLZO solid electrolyte adhered thereto obtained in Examples 1-3 and Comparative Examples 1-6, respectively, under the same experimental conditions.
[0063]
[0064]
[0065] As can be seen from the above table, the performance of the carrier 100 in Examples 1-3 is better than that of the carrier in Comparative Examples 1-6. This indicates that when the second coating 106 is a polysiloxane-grafted acrylic resin, the performance of the carrier 100 is better. For example, the coating has no cohesive appearance, good flatness, is easier to peel, and has greater adhesion. The results of Examples 1-3 also show that the best effect is achieved when the mass proportion of polysiloxane is 1%; when the mass proportion of polysiloxane increases to 5%, the performance decreases. Preferably, when the second coating 106 is a silicone-grafted acrylic resin layer, the mass proportion of silicon in the silicone-grafted acrylic resin layer is 1% to 3%.
[0066] Please also refer to Figure 2-3 , which are photos of the LLZO solid electrolyte coated on the carrier surface in Examples 1 and 2, respectively. It can be seen from the figures that the carrier does not produce edge shrinkage, and the LLZO solid electrolyte has good film-forming properties on the carrier surface.
[0067] The present invention also provides a method for preparing the oxide solid electrolyte carrier 100, comprising the following steps:
[0068] Step S1, providing the substrate 102, an adhesive and a resin material;
[0069] Step S2, coating the adhesive on the surface of the substrate 102 and baking to form the first coating 104; and
[0070] In step S3 , the resin material is coated on the surface of the first coating layer 104 , and baked to form the second coating layer 106 , thereby obtaining the oxide solid electrolyte carrier 100 .
[0071] In step S1, the substrate 102 may be further surface treated to remove impurities on the substrate surface. The substrate 102 is capable of withstanding the baking temperatures in steps S2 and S3, as well as the baking temperature after the oxide solid electrolyte gel is applied to the surface of the carrier 100 during use. Preferably, at the aforementioned baking temperatures, the thermal shrinkage of the substrate 102 in both the machine direction (MD) and the transverse direction (TD) is less than 0.5.
[0072] In step S2, the adhesive is preferably a functionalized adhesive layer. More preferably, the adhesive is a polyethylene (PE) functionalized adhesive layer. The PE functionalized adhesive layer provides functionalized bite force to properly bond the substrate 102 and the second coating 106, thereby allowing the solid electrolyte carrier 100 to exhibit a characteristic surface energy.
[0073] In the above step, the baking temperature can be selected according to the type of the binder. In this embodiment, the binder is polyethyleneimine (PEI), the degree of polymerization of PEI is about 90-110, the monomer molecular weight is 43, and the baking temperature is 120°C.
[0074] In step S3, the resin material is preferably a silicone grafted resin layer. More preferably, the resin material is a silicone grafted acrylic resin (methyl acrylate).
[0075] In the above step, the baking temperature can be selected according to the type of the resin material. In this embodiment, the resin material is polysiloxane-grafted acrylic resin, and the baking temperature is 150°C.
[0076] During use, the oxide solid electrolyte gel is evenly coated on the surface of the second coating layer 106 and then baked to form an oxide solid electrolyte film on the surface of the carrier 100. In this embodiment, the oxide solid electrolyte is a nano-sized LLZO composite polymer colloid with a solid content greater than 30% and an LLZO particle size less than 100 nm. The coating thickness is 20 to 80 μm, and the baking temperature is 120 to 180°C.
[0077] The oxide solid electrolyte carrier provided by the present invention includes a substrate, a functionalized adhesive layer, and a silicone-grafted acrylic coating. The adhesive layer provides functionalized bite force, appropriately bonding the substrate and the acrylic coating, so that the carrier exhibits a characteristic surface energy that matches that of the oxide solid electrolyte. This allows the oxide solid electrolyte colloid to be effectively coated and bite-bonded on the surface of the oxide solid electrolyte carrier, and then, through a series of baking processes, forms an oxide solid electrolyte film on the surface of the carrier. The oxide solid electrolyte film can be effectively attached to the carrier, and experiments have shown that it does not cause problems such as shrinkage, warping, peeling, and baking beam marks. Moreover, when used, the oxide solid electrolyte film can be easily torn off the carrier without causing structural damage to the oxide solid electrolyte film.
[0078] The above description is a few specific embodiments of the present application, but in actual application, it is not limited to these embodiments. Those skilled in the art may also make other changes within the spirit of the present invention. Of course, these changes made in accordance with the spirit of the present invention should be included in the scope of protection claimed by the present invention.
Claims
1. An oxide solid electrolyte membrane carrier, characterized in that: The invention comprises a substrate, a first coating layer and a second coating layer, wherein the first coating layer is coated on the surface of the substrate, the second coating layer is coated on the surface of the first coating layer, the first coating layer is an adhesive layer, and the second coating layer is a resin layer.
2. The oxide solid electrolyte membrane carrier according to claim 1, wherein The substrate has a heat shrinkage ratio of less than 0.5 in both a machine direction (MD) and a transverse direction (TD) after being maintained at a temperature greater than or equal to 160° C. for 10 minutes.
3. The oxide solid electrolyte membrane carrier according to claim 1, wherein The substrate is made of polyethylene terephthalate (PET), polyimide (PI), polypropylene (PP), propylene oxide (PO), triacetyl cellulose (TAC), or cycloolefin polymer (COP).
4. The oxide solid electrolyte membrane carrier according to any one of claims 1 to 3, wherein The thickness of the substrate ranges from 120 to 130 μm.
5. The oxide solid electrolyte membrane carrier according to any one of claims 1 to 3, wherein The first coating is a functionalized bonding layer.
6. The oxide solid electrolyte membrane carrier according to claim 5, characterized in that The first coating layer is a polyethyleneimine (PEI) layer.
7. The oxide solid electrolyte membrane carrier according to any one of claims 1 to 3, characterized in that The second coating layer is a silica gel grafted resin layer.
8. The oxide solid electrolyte membrane carrier according to claim 7, characterized in that The second coating layer is a silicone-grafted acrylic resin (methyl acrylate).
9. The oxide solid electrolyte membrane carrier according to claim 8, characterized in that The mass proportion of silicon in the silica gel grafted acrylic resin layer is 1% to 3%.
10. The oxide solid electrolyte membrane carrier according to claim 8, wherein The second coating layer is polysiloxane-grafted acrylic resin.
11. A method for preparing an oxide solid electrolyte membrane carrier according to any one of claims 1 to 3, comprising the following steps: Providing the substrate, a binder and a resin material; Applying the binder on the surface of the substrate and baking to form the first coating; as well as The resin material is coated on the surface of the first coating layer and baked to form the second coating layer, thereby obtaining the oxide solid electrolyte carrier.